Produksi β-Glukosidase Aspergillus niger BIO 2173 dengan Fermentasi Padat Menggunakan Substrat Dedak - Sri Sugiwati; Maggy Thenawidjaja Suhartono; Muhammad Hanafi; Hanifah Nuryani Lioe (JURNAL SELULOSA, 2018)
Production of β-Glucosidase Aspergillus niger BIO 2173 on Solid State Fermentation Using Rice Bran as SubstrateAbstractβ-Glucosidase (EC 3.2.1.21) is a part of the cellulase enzyme complex which acts synergistically with exoglucanase and endoglucanase to hydrolyze cellulose into glucose. The purpose of this study was to obtain the maximum fermentation conditions for production of b-glucosidase Aspergillus niger BIO 2173 with solid state fermentation using rice bran as fermentation substrate. The factors that affect the production of b-glucosidase which consist of initial pH of the fermentation medium, incubation period, ratio of water content to fermentation substrate, incubation temperature and addition of the Mandel’s mineral salts solution were examined in the study. The results showed that maximum fermentation conditions for β-glucosidase production were at initial of fermentation pH of 2,0, incubation period of 7 days, ratio of water content to substrate of 1:1, and incubation temperature of 32oC. Addition of Mandel’s mineral salts solution to the fermentation substrate at maximum fermentation conditions increased the activity and specific activity of β-glucosidase crude extract up to 5,24 ± 0,57 U/mL and 2,46 ± 0,04 U/mg, respectively.Abstrakβ-Glukosidase (EC 3.2.1.21) merupakan bagian dari enzim multi kompleks selulase, yang bekerja secara sinergis dengan eksoglukanase dan endoglukanase menghidrolisis selulosa menjadi glukosa. Tujuan dari penelitian ini adalah mendapatkan kondisi fermentasi maksimum untuk produksi β-glukosidaseAspergillus niger BIO 2173 dengan fermentasi media padat menggunakan substrat dedak. Pengujian dilakukan terhadap faktor-faktor yang mempengaruhi produksi b-glukosidase, yaitu pH awal medium fermentasi, waktu inkubasi, perbandingan kandungan air terhadap substrat medium fermentasi, suhu inkubasi dan penambahan larutan garam mineral Mandels. Hasil penelitian menunjukkan bahwa kondisi fermentasi maksimum untuk produksi b-glukosidase adalah pada pH awal medium fermentasi 2,0; waktu inkubasi 7 hari, perbandingan kandungan air terhadap substrat medium fermentasi 1:1, dan suhu inkubasi 32oC. Penambahan larutan garam mineral Mandels ke dalam substrat fermentasi pada kondisi fermentasi maksimum menyebabkan peningkatan aktivitas dan aktivitas spesifk ekstrak kasar b-glukosidase masing-masing sebesar 5,24 ± 0,57 U/mL dan 2,46 ± 0,04 U/mg protein. Kata kunci: β-glukosidase, Aspergillus niger, dedak padi, fermentasi padat, ekstrak kasar